GAMBARAN TINGKAT PENGETAHUAN TENTANG STROKE PADA PENDERITA HIPERTENSI SELAMA MASA PANDEMI COVID-19 - Ulfa Rahmadini; Wasisto Utomo; Widia Lestari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2022)
Hypertension is the most common comorbid in Covid-19 so patients are expected to be able to modify their lifestyle and change their health behavior to manage hypertension. Uncontrolled hypertension is the leading risk factor that causes stroke so prevention efforts are needed that aim to prevent and reduce complications such as stroke. During the pandemic, efforts to prevent complications such as gymnastics and health education will no longer be carried out. The Covid-19 pandemic has made patients afraid to go to health services. This study aims to describe the level of knowledge about stroke in patients with hypertension during the covid-19 pandemic.This research was quantitative research with descriptive method. The sample used in this study was 100 people with convenience sampling technique. The results of the univariate test showed that the most people with hypertension were 55-65 years old (47.0%), the most gender were women (54.0%), the most education was high school (46.0%), the majority of hypertension sufferers did not work as much as (79.0%), the longest-suffering from hypertension was 1-5 years (40.0%), and the majority lived with their families (98.0%). Based on the results of this research, frequency of the level of knowledge about stroke in poor category was 69 people (69.0%), and in good category was 31 people (31.0%). As input for health facilities to increase awareness of stroke complications in patients with hypertension and further researchers can investigate further about the factors that affect the level of knowledge.Keywords : covid-19; hypertension; level of knowledge; stroke.